2018
DOI: 10.1016/j.ajur.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Update on minimally invasive surgery and benign prostatic hyperplasia

Abstract: Transurethral resection of the prostate (TURP) became the gold standard surgical treatment for benign prostatic obstruction without undergoing randomized controlled trials against the predecessor standard in open suprapubic prostatectomy. TURP has historically been associated with significant morbidity and this has fuelled the development of minimally invasive surgical treatment options. Improvements in perioperative morbidity for TURP has been creating an ever increasing standard that must be met by any new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…TURP as previously documented became the 'gold standard' surgical treatment for BPH [10,11,[26][27][28], thus the present study evaluated the outcome of patients with LUTS secondary to BPH (LUTS/BPH) using transperineal intraprostatic BoNT-A injection in comparison to TURP. Patients in the BoNT-A group received 200 U BoNT-A, the choice of the injection dose was dependent on previous findings; Crawford et al [29] found that BoNT-A injection of 100 or 300 U BoNT-A is effective and safe, but the 100 U dose may be preferable due to similar efficacy with reduced costs and adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…TURP as previously documented became the 'gold standard' surgical treatment for BPH [10,11,[26][27][28], thus the present study evaluated the outcome of patients with LUTS secondary to BPH (LUTS/BPH) using transperineal intraprostatic BoNT-A injection in comparison to TURP. Patients in the BoNT-A group received 200 U BoNT-A, the choice of the injection dose was dependent on previous findings; Crawford et al [29] found that BoNT-A injection of 100 or 300 U BoNT-A is effective and safe, but the 100 U dose may be preferable due to similar efficacy with reduced costs and adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…A nickel-titanium alloy, or nitinol, device aims to relieve LUTS due to BPH by using expanded struts that exert a radial force [21]. The radial force compresses obstructive prostatic lobes causing local ischemic necrosis of the urethral mucosa [22].…”
Section: Temporary Implantable Nitinol Devicementioning
confidence: 99%
“…The least studied technique thus far, histotripsy uses high intensity ultrasound technology to vaporize fluid in prostatic tissues and release gaseous microbubbles which cause tissue destruction [7,21,41]. In animal studies with canines by Darnell et al [42] in 2015 found that histotripsy caused 31% decrease in prostate volume with limited inflammation and fibrosis.…”
Section: Histotripsymentioning
confidence: 99%
See 2 more Smart Citations